Parental perspectives regarding primary‐care weight‐management strategies for school‐age children. Issue 2 (10th April 2014) - Turer, Christy Boling; Mehta, Megha; Durante, Richard; Wazni, Fatima; Flores, Glenn
Abstract: To identify parental perspectives regarding weight‐management strategies for school‐age children, focus groups were conducted of parents of overweight and obese (body mass index ≥ 85th percentile) 6–12‐year‐old children recruited from primary‐care clinics. Questions focused on the role of the primary‐care provider, effective components of weight‐management strategies and feasibility of specific dietary strategies. Focus groups were recorded, transcribed and analysed using margin coding and grounded theory. Six focus groups were held. The mean age (in years) for parents was 32, and for children, eight; 44% of participants were Latino, 33%, African–American and 23%, white. Parents' recommendations on the primary‐care provider's role in weight management included monitoring weight, providing guidance regarding health risks and lifestyle changes, consistent follow‐up and using discretion during weight discussions. Weight‐management components identified as key included emphasising healthy lifestyles and enjoyment, small changes to routines and parental role modelling. Parents prefer guidance regarding healthy dietary practices rather than specific weight‐loss diets, but identified principles that could enhance the acceptability of these diets. For dietary guidance to be feasible, parents recommended easy‐to‐follow instructions and emphasising servings over counting calories. Effective weight‐management strategies identified by parents include primary‐care provider engagement in weight management, simple instructions regarding healthy lifestyle changes, parental involvement and deemphasising specific weight‐loss diets. These findings may prove useful in developing primary‐care weight‐management strategies for children that maximise parental acceptance.